Cost and Health Care Utilization in ARDS—Different from Other Critical Illness? - Bice, Thomas; Cox, Christopher E.; Carson, Shannon S. (Seminars in Respiratory and Critical Care Medicine, 2013)
Costs of care in the intensive care unit are a frequent target for concern in the current health care system. Utilization of critical care services in the United States is increasing and will continue to do so. Acute respiratory distress syndrome (ARDS) is a common and important complication of critical illness. Patients with ARDS frequently have long hospitalizations and consume a significant amount of health care resources. Many patients are discharged with functional limitations and high susceptibility to new complications that require significant additional health care resources. There is increasing literature on the cost-effectiveness of the treatment of ARDS, and despite its high costs, treatment remains a cost-effective intervention by current societal standards. However, when ARDS leads to prolonged mechanical ventilation, treatment becomes less cost-effective. Current research seeks to find interventions that lead to reductions in duration of mechanical ventilation and intensive care unit (ICU) length of stay. Limited reductions in ICU length of stay have benefits for the patient, but they do not lead to significant reductions in overall hospital costs. Early discharge to post–acute care facilities can reduce hospital costs but are unlikely to decrease costs for an entire episode of illness. Improved effectiveness of communication between clinicians and patients or their surrogates could help avoid costly interventions with poor expected outcomes.
Keywords: ARDS; mechanical ventilation; critical care; costs and cost analysis